SUSTAINABLE FINANCE STRATEGY: BUILDING A STRONGER BUSINESS - Loso Judijanto; Dedi Harianto; Silvia Ekasari (Jurnal Ekonomi dan Bisnis, 2024)
In the modern business context, the urgency to integrate sustainability into the core of corporate strategy has increased significantly. This study aims to investigate how sustainable finance strategies can build stronger businesses, increase resilience, and ensure long-term development. The research method used in this study is literature by searching for references in accordance with the context of the research. The results show that sustainable finance strategies have significant positive impacts on various aspects of business performance. First, companies that adopt these strategies show greater resilience to economic fluctuations and environmental changes, thanks to better diversification and risk management. Second, sustainable finance strategies create better access to capital, both through green financial instruments and through enhanced corporate reputation. Thirdly, sustainability drives innovation and operational efficiency, resulting in cost reduction and improved profit margins. Finally, research shows a positive relationship between sustainable finance and regulatory compliance, as well as long-term value creation for all stakeholders.